Penciptaan Film Animasi “Chase!” Dengan Teknik “Digital Drawing” - Febri Faizin Alfatra; Mahendradewa Suminto; Pandan Pareanom Purwacandra (Journal of Animation and Games Studies, 2019)
A short animation that combines several personal experiences and surroundings into a simple yet entertaining story. Although the story is presented simply, visualization is made unique and flexible with digital two-dimensional animation techniques. This animated film is titled “CHASE!” Which means chasing, taken from the core of the film which tells the story of a young man who chases a mysterious woman who turns out to be a transvestite.The animated film “CHASE!” Lenght 3 minutes 45 seconds, make the story made shorter and directly to the point at the core of what will be delivered. The number of shots reached 45 shots with a total of 5400 frames of HDTV 1920 x 1080 px 24 fps (frames per second). In the process of making this film also applied 12 principles of animation. Making an animated film “CHASE!” uses a digital process in it. For animating, 2D drawing frame by frame technique are used digitally by using computers, background images are also digitally created without leaving the artistic value of traditional drawing techniques using hands.Keywords: Film, 2D Animation, Personal Experience, Digital